Elizabeth Bowen : Feminist Discourse and the Italian Neorealism - Sanches, Zuzanna (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
This paper will analyze the relationship between Elizabeth Bowen’s Eva Trout and the theoretical tenets of Italian neorealist cinematography. The exchange between the novel and neorealism can be found in the concept of time-image that builds upon an evolution from doer to seer, and in the use of so far marginalised figures, namely that of a child and of a woman. Bodily movement does not lead towards a conclusion, but rather a multiplication within the mental range of subjective, somewhat tiresome narratives. As such, there is another time within the subject which constitutes a kind of propelling power to delineate reality. The character must labour to comprehend the images/visions, and these very endeavours or ‘concatenations’ become the embedding time-space. Time is indeterminate and multiple as the subject upon which it hinges. The fluid and constant intertwining of life and art always fascinated Elizabeth Bowen’s imagination. To her, the language of aesthetic creation merged with the witchcraft and magic of film, creating fictions not confined to gender limitations and free from rigid cultural entanglements. In such realizations of art, Bowen could concede the subject a greater participation in the process of creation (from a feminist perspective, by opening onto the affective powers of otherness and agency). By the same token, it was at the crossroads of cinema and literature that she, I believe, found her definition of a female new voice.